Identification, Isolation and Pathological Changes Associated with Natural Cases of Avian Colibacillosis in Assam - Tella, Udaya Sai Sitaram; Buragohain, Mridusmrita; Deka, Abhijit; Reddy, Sravan Kumar; Srikanth, Sreeramdas; Umar, Md; Ahmed, Rofique. (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study deals with the pathological changes associated on natural cases of avian colibacillosis in Assam for a period of one year that is from January 2022 to December 2022. During year 2022, an incidence of colibacillosis was recorded high in the month of July and August in the carcasses brought to the Department of Pathology, CVSc, AAU, Khanapara. The mortality was 6.4% (i.e., 94) considering only among the month of April (with 4.2%), May (with 9.5%), June (with 18%), July (with 40%), and August (with 27%) and were diagnosed as Avian Colibacillosis. Among the 1,449 samples collected from both commercial layer and broiler flock 94 samples revealed isolates of colibacillosis. Molecular confirmation of the isolates, using 16SrNA gene suitable for identification of colibacillosis. The effect of different breed, colony morphology, biochemical properties on the occurrence of colibacillosis were also studied. Mostly observed gross lesions include changes that were found on heart include deposition of fibrinous exudate on the pericardial surface and pericardial thickening associated with pericarditis. Histopathologically, heart showed heavy infiltration of mononuclear phagocytic cells in myocardial fibres resulting in severe myocarditis and in the epicardium, fibrin deposition was present mixed with infiltrating cells.
Keywords: 16S rRNA; Avian colibacillosi; Breed; Colony morphology; Month; Pericarditis